1974
DOI: 10.1002/aic.690200415
|View full text |Cite
|
Sign up to set email alerts
|

Surface diffusion of stearic acid on aluminum oxide

Abstract: By means of infrared internal reflection spectroscopy we measured the time dependence of the surface concentration of stearic acid molecules over a well defined region of the surface. The molecules were diffusing into this region from a source comprising a compressed monolayer or bulk crystalline material outside the field of view. By these measurements in conjunction with solutions to the diffusion equations we determined the diffusion coefficient D, of stearic acid on the (0001) plane of a-alumina.We also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The rate expression for diffusion of oxy-carbon species on Al 2 O 3 is therefore given by eq : which represents the average diffusion rate of all the different oxy-carbon surface species. The value of E a from this work (24 kJ/mol) is within the range of values previously reported for diffusion of carbonaceous species on different phases of Al 2 O 3 : 5 kJ/mol for propene diffusion on η-Al 2 O 3 ; 8–12 kJ/mol for CO 2 diffusion on γ-Al 2 O 3 ; 12 kJ/mol for benzene diffusion on η-Al 2 O 3 ; and 109 kJ/mol for stearic acid diffusion on α-Al 2 O 3 …”
Section: Resultssupporting
confidence: 87%
“…The rate expression for diffusion of oxy-carbon species on Al 2 O 3 is therefore given by eq : which represents the average diffusion rate of all the different oxy-carbon surface species. The value of E a from this work (24 kJ/mol) is within the range of values previously reported for diffusion of carbonaceous species on different phases of Al 2 O 3 : 5 kJ/mol for propene diffusion on η-Al 2 O 3 ; 8–12 kJ/mol for CO 2 diffusion on γ-Al 2 O 3 ; 12 kJ/mol for benzene diffusion on η-Al 2 O 3 ; and 109 kJ/mol for stearic acid diffusion on α-Al 2 O 3 …”
Section: Resultssupporting
confidence: 87%
“…Yang et al (1974) found that stearic acid had a surface diffusivity on alumina of about 10 -9 -10 -11 m 2 s -1 depending on the hydration degree of the alumina. Allara and Nuzzo (1985) reported values of D s of 10 -10 -10 -11 for different alkanoic acids on alumina.…”
Section: Mass Transfer Kinetics and Models For Adsorption In The Liqumentioning
confidence: 99%
“…The final result is 66 l/(mole)(cm). Given the fact that the first two o r three CH, groups will be perturbed by the surface and therefore have a lower than average extinction coefficient, the agreement with the peak molar extinction coefficient of 77 l/(mole) (cm) per methylene group for the asymmetric stretch of n-alkanes measured in CC1, solution [17] is fairly good.…”
Section: Irs Applied To Model Systemsmentioning
confidence: 61%